The Role of E-Governance on Corruption in East Asia & Pacific: A Panel Data Analysis - Bhatti, Muhammad Azhar; Hashmi, Shah Rukh; Hussain, Altaf; Ahmad, Tusawar Iftikhar (Pakistan Journal of Humanities and Social Sciences, 2024)
This study seeks to assess the influence of e-governance on corruption and the various aspects of governance quality within the East Asia and Pacific region. This research employs the CS-ARDL model to evaluate the short- and long-term impacts of e-governance, political stability, regulatory quality, Voice and accountability, and the legal environment on governance indicators, particularly corruption. The results confirm that e-governance influences improvements in transparency and accountability, thereby highlighting the issue of corruption. The primary determinants of governance effectiveness encompass political stability, regulatory quality, and Voice and accountability. Political stability is observed to facilitate reforms and not hinder innovation. Regularity, quality, Voice, and accountability foster a governance environment that mitigates corrupt practices. Economic growth and population size also affect the infection rate, though their impact is less significant than that of poverty rates. It is recommended that policymakers enhance e-governance structures, establish robust legal and regulatory frameworks, and augment citizen voice and accountability. Additional research may explore the variations in e-governance effectiveness in addressing corruption across different sectors, the impact of e-governance on Governance in various countries, and the potential applications of advanced technologies like blockchain. The evidence provides practical guidance for policymakers in the World Bank's East Asia and Pacific region by delineating methods through which e-governance and institutional change can enhance Governance and mitigate corruption.